Role of mental training in sports performance: A critical appraisal - Pramanik, P.; Chatterjee, S. (International Journal of Research Pedagogy and Technology in Education & Movement, 2024)
Mental training is very much in vogue, yielding sterling results in sports and athletic performances. A growing body of research in this area constantly exemplifies that mental training is becoming an indispensable part in athletic preparation programme, particularly when physical training inevitably becomes more and more one-sided approach to build a complete athlete. The main objective of this review article is to investigate and understand the role of mental training in sports performance. Studies that matched and fulfilled the primary objective of the article were considered, reviewed, presented systematically and interpreted critically. Different types of mental technique such as self-talk, imagery, goal setting, physical relaxation, biofeedback, mindfulness training, yoga based mental training and cognitive training have been reported as instrumental to enhance sports performance. Mental training develops an athlete`s different psychological skills such as recovery skills, volitional skills, arousal regulation skills, copping skills, motivational skills, perceptual cognitive skills, motor control skills, self-skills and life skills. These skills help an athlete to overcome different difficult situations in the competition and motivate to set a high aspiration. This review study unfolds some fundamental concepts of mental training and its application to nurture and prepare an athlete for better performance.